Teaching experiences during the SARS-COV-2 pandemic in a Brazilian School of Dentistry - Gomes, Brenda Paula Figueiredo de Almeida (2020)
The coronavirus outbreak (2019) represents apublic health emergency of global concern. Several measureshave been taken to minimise the risk of infection amongthe population, including social distancing, working fromhome, closure of non-essential activities since the detectionof the first case in Brazil. This study describes the teachingexperiences during the SARS-COV-2 pandemic in a BrazilianSchool of Dentistry. The State University of Campinas(UNICAMP) was the first public university in Brazil to stopall the classroom activities on 13th of March 2020 due toCOVID-19, followed by other universities. UNICAMP developedseveral initiatives and created a special support page fordigital teaching, where it is possible to obtain guidance,support materials for teachers and a space for exchangingmessages (e-mail and chat) for specific guidelines. UNICAMPhas started lending computer equipment to undergraduateand graduate students according to socioeconomic criteria.Along with the equipment, 500 chips have been delivered with10 GB of internet so that these students are able to accessthe network and carry out the remote activities related to theircourses. In conclusion, quality education is the key-elementin forming high-quality professionals that will in a near futureprovide health care for the community, be part in internationalresearch groups and become lecturers.